Ureteral stent tube based on bacterial cellulose composite coating and preparation method thereof
Through the composite technology of bacterial cellulose and degradable fiber braided tube, a folded three-layer structure ureteral stent tube is formed, which solves the urinary tract damage and infection caused by existing non-degradable materials, and achieves the effect of safe degradation and urinary tract healing.
Patent Information
- Application Number
- CN202210144587.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-17
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-02-17
AI Technical Summary
The existing ureteral stent tube materials are not degradable, and long-term use in the body can lead to urinary tract tissue damage, infection and edema, and urinary tract complications are easily caused during extubation.
Bacterial cellulose is combined with the degradable fiber braided tube to form a three-layer hollow tubular structure ureteral stent tube. The bacterial cellulose membrane is folded over the braided tube to prevent degradation of degraded debris from falling off.
It realizes safe degradation of ureteral stent tubes, avoids safety problems caused by degraded debris, reduces surface friction, promotes urinary tract healing, and has antibacterial and immune regulation functions.
Smart Images

Figure CN114668899B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical devices and relates to a ureteral stent tube based on bacterial cellulose composite coating and a preparation method thereof. Background Art
[0002] Ureteral stents are widely used in urological surgery, mainly for kidney stones, hydronephrosis, ureteral tumors, kidney transplantation and dilation treatment of ureteral stenosis. After being implanted in the ureter, it can play an important role in draining urine and preventing ureteral stenosis and adhesion blockage. Currently, ureteral stents used in clinical practice are mostly made of silicone rubber or polyurethane polymer composite materials that cannot be degraded in the human body. There are some insurmountable defects in clinical application, such as: they must be removed through invasive operations, that is, through cystoscopy. Although this type of cystoscopy operation is not considered a major operation, it will cause great pain to the patient. What is more serious is that when the tube is removed, it will cause varying degrees of damage to the urinary tract tissue, causing infection and edema, and often requires emergency treatment.
[0003] The retention time of ureteral stents is generally 4 weeks, and the existing ureteral stents in clinical practice are all non-degradable polyurethane stents. After 4 weeks, a second operation is required to remove the stent, which damages the patient's urinary system. If the stent is placed for a long time, it will lead to more serious consequences, such as loss of renal function, and even the need to remove the kidney. It causes serious physical, mental and economic damage to the patient. Non-degradable ureteral stents also often cause some complications. As the retention time of the ureteral stent increases, these composite materials begin to affect the urothelium and urine components, resulting in the formation of coatings and bacterial biofilms around the ureteral stents, and causing infection. This is all due to the foreign body reaction caused by the non-degradable catheter in the body for a long time. In addition, the surface friction coefficient of the silicone rubber ureteral stent is high, which makes it difficult to insert the catheter during surgery, and it is easy to slide after being inserted into the body, which cannot meet the requirements of practical applications.
[0004] In the past few decades, the research and clinical application of degradable urethral and ureteral stents have been developed and have been more widely used. The main materials are PLA, PGA and PLLA or PLGA. Depending on the material and process, the degradation time is 2 to 12 months. In the previous studies, a single material was used, and the obtained stent tubes were often difficult to control the degradation time, with poor mechanical properties and poor elasticity. After the use of composite materials, the situation has improved. For example, Chinese patent CN103041454B uses L-lactide / ε-caprolactone copolymer and cross-linked polyvinyl pyrrolidone as raw materials, and a degradable ureteral stent is obtained by co-extrusion. The addition of polyvinyl pyrrolidone greatly reduces the wet friction on the surface of the stent tube, and increases the degradation rate, prompting the degradable components to disintegrate into small fragments, and to a certain extent avoids the degradation fragments from blocking the ureter. Chinese patent CN102266594B uses two PGA and PGLA fibers with different degradation rates as raw materials to weave into a tube, and chitosan is coated inside the tube to obtain a gradually degradable braided ureteral stent. Chinese patent CN103211671B adds a heat treatment process on the basis of braiding into a tube, so that the low-melting-point components in the tube wall fiber material are melted into a film, and are tightly and evenly combined with other fiber components in the tube wall to strengthen the wall of the braided tube. The prepared ureteral stent tube has both the excellent axial stretching and flexibility of the fiber stent tube and the good mechanical support performance of the membrane material stent tube. In summary, these methods have solved the problems of gradual degradation and mechanical strength to a certain extent, but from a structural point of view, the problem of safety of fragments related to degradation of the tube wall material still exists. For example, it is reported that Boston Scientific has developed a degradable ureteral drainage system based on bioabsorbable sodium alginate, which will be maintained for 48 hours before degradation, but faces serious problems in clinical trials of residual fragments, which have led to the termination of the project. Therefore, in the design of ureteral stent tubes, it is necessary to fundamentally avoid this problem. Summary of the invention
[0005] The purpose of the present invention is to solve the above problems existing in the prior art and to provide a ureteral stent tube based on bacterial cellulose composite coating and a preparation method thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A ureteral stent tube based on bacterial cellulose composite coating is a three-layer hollow tubular structure, the middle layer is a degradable fiber braided tube, the outer layer and the inner layer are tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II, respectively, and the tubular bacterial cellulose membrane I and the tubular bacterial cellulose membrane II are respectively attached to the inner and outer walls of the degradable fiber braided tube;
[0008] The tubular bacterial cellulose membrane I and the tubular bacterial cellulose membrane II are formed by folding the hollow tubular bacterial cellulose membrane III from one end to the other end along the length direction, and the length of the tubular bacterial cellulose membrane I is half of that of the hollow tubular bacterial cellulose membrane III.
[0009] The material used for coating the degradable fiber braided tube in the present invention is bacterial cellulose (BC), which is a natural nanofiber material obtained by bacterial fermentation and has great application potential in the biomedical field. BC is very similar to natural plant cellulose in terms of chemical composition and fiber structure. Both are composed of glucose groups connected by β-1,4-glycosidic bonds to form a main chain and polymerized into a polymer. However, the purity of BC is very high and does not contain accompanying products such as lignin, pectin and hemicellulose. During static culture, BC forms a hydrogel-like film with a three-dimensional structure in the form of random coils of nanofiber bundles, and the water content can reach more than 99%. BC has extremely strong strength and tear resistance, and its elastic modulus can reach dozens of times that of ordinary plant fibers; BC has higher mechanical strength, high tensile strength and elastic modulus; a large number of hydroxyl groups on the surface of nanofibers make bacterial cellulose have high water retention and high wet strength. BC has good biocompatibility, biodegradability, good cell compatibility with various cells, and can promote cell proliferation and growth.
[0010] As the preferred technical solution:
[0011] As described above, in a ureteral stent tube based on bacterial cellulose composite coating, the outward surface of the tubular bacterial cellulose membrane I has a plurality of parallel and evenly arranged rectangular grooves (the shape of the grooves includes but is not limited to rectangles, and can also be semicircular, conical, etc.), and the length direction of the rectangular grooves is parallel to the axial direction of the tubular bacterial cellulose membrane I, which is beneficial to reduce the surface friction during insertion and removal from the urethra, and the surface of the tubular bacterial cellulose membrane II is smooth.
[0012] In the above-mentioned ureteral stent tube based on bacterial cellulose composite coating, the degradable fiber braided tube is obtained by using a diamond braiding or regular braiding method to braid degradable fibers capable of sustained-release functional substances. The diamond braiding or regular braiding method can appropriately reduce the wall thickness of the tube;
[0013] The degradable fiber capable of sustained-release of functional substances is a blended fiber of synthetic fiber and chitosan fiber, the synthetic fiber is PLA, PLGA, PGA, PCL or polydioxanone fiber, the synthetic fiber contains silver ions or nanosilver particles, and the chitosan fiber contains copper ions and zinc ions.
[0014] In the bacterial cellulose composite-coated ureteral stent described above, the content of chitosan fiber in the degradable fiber capable of sustained-release of functional substances is 3 to 15 wt %;
[0015] The content of zinc ion is 0.1-5wt% of the chitosan fiber, and the molar ratio of zinc ion to copper ion is 2:1-1.4; the content of silver ion or nano silver particle is 0.1-2wt% of the chitosan fiber.
[0016] Zinc ion (Zn 2+ ) is an essential component of enzymes that maintain protein structural integrity and regulate gene expression. It participates in the regulation of immunity, cell growth and migration and plays a key role in tissue healing. Therefore, it requires zinc ions to be able to run through the entire tissue healing process and to meet the requirements of a large amount of release in the early stage and to have a good sustained release capacity in the middle and late stages. In the proliferation and remodeling stages of tissue healing, copper ions (Cu 2+ ) can induce the expression of vascular endothelial growth factor, promote angiogenesis, and maintain the stability of collagen. Silver ions or nanosilver particles have good antibacterial effects.
[0017] In the above-mentioned ureteral stent tube based on bacterial cellulose composite coating, the length of the rectangular groove is equal to the length of the tubular bacterial cellulose membrane I, the width is 50-200nm, the height is 50-100nm, and the spacing between two adjacent rectangular grooves is 50-200nm. The size of the rectangular groove is mainly set based on the experience of existing studies. Such a micro-nano scale can be recognized by endothelial cells, and endothelial cells will grow and proliferate rapidly along the groove, thereby achieving rapid endothelialization and reducing the production of scar tissue.
[0018] As described above, the ureteral stent tube based on bacterial cellulose composite coating has a length of 15 to 40 cm and a diameter of 1.5 to 3.5 mm; the wall thickness of the ureteral stent tube is 0.1 to 0.5 mm, wherein the wall thickness of the degradable fiber woven tube of the middle layer is 0.08 to 0.45 mm, and the wall thickness of the tubular bacterial cellulose membrane I and the tubular bacterial cellulose membrane II is the same, generally 0.02 to 0.2 mm.
[0019] The present invention also provides a method for preparing a ureteral stent tube based on bacterial cellulose composite coating, firstly preparing a hollow tubular bacterial cellulose membrane III, then weaving degradable fibers on the outer wall of the hollow tubular bacterial cellulose membrane III to form a degradable fiber braided tube, and finally folding the hollow tubular bacterial cellulose membrane III from one end to the other end along the length direction to form a tubular bacterial cellulose membrane I and a tubular bacterial cellulose membrane II, so that the degradable fiber braided tube is located between the tubular bacterial cellulose membrane I and the tubular bacterial cellulose membrane II, so as to prepare a ureteral stent tube based on bacterial cellulose composite coating;
[0020] The woven region of the degradable fiber is the outer wall of the tubular bacterial cellulose membrane II.
[0021] As the preferred technical solution:
[0022] According to the method described above, the specific steps for preparing the ureteral stent tube based on bacterial cellulose composite coating are as follows:
[0023] (1) The fermentation strain and the fermentation culture medium are uniformly mixed and placed in a hollow tubular fermentation device. After fermentation for 5 to 9 days, the hollow tubular bacterial cellulose membrane III is obtained by purification treatment. The hollow tubular fermentation device is a double-layer jacketed tube, and the inner layer has an oxygen permeability (the test standard for oxygen permeability is GB / T 1038-2000, "Plastic Film and Sheet Gas Permeability Test Method Pressure Difference Method") of 1 to 10×10 5 cm 3 / 24h·0.1MPa silica gel film, the fermentation strain and the fermentation culture medium are placed between the double layers of the hollow tubular fermentation device, and the inner layer of the hollow tubular fermentation device is filled with mixed gas, and the pressure of the mixed gas is 1.1~1.5×10 5 Pa, the volume proportion of oxygen in the mixed gas is 25-40% (the purpose of this setting: 1. The fermentation strain is an aerobic bacteria, and the fermentation speed will be increased under the condition of sufficient oxygen; 2. The use of mixed gas is mainly for cost and benefit considerations, and other gases in the mixed gas are inert gases, etc.; 3. Maintaining a certain pressure can make oxygen pass through the silica gel film better, and at the same time make the bacterial cellulose nanofibers obtained by fermentation in the part in contact with the silica gel film more dense and smooth on the surface); the hollow tubular fermentation device is divided into two hollow tubular objects A and B, the silica gel film of the inner layer of the hollow tubular object A has a smooth surface, and the silica gel film of the inner layer of the hollow tubular object B has a patterned structure on the outward surface; the patterned structure refers to a plurality of rectangular protrusions formed on the surface of the silica gel film by using micro / nano forming patterning technology, which are parallel and evenly arranged along the axis of the hollow tubular object B, the length of the rectangular protrusion is equal to the length of the hollow tubular object B, the width is 50-200nm, the height is 50-100nm, and the spacing between two adjacent rectangular protrusions is 50-200nm;
[0024] (2) placing a polytetrafluoroethylene rod in the purified hollow tubular bacterial cellulose membrane III (since pure bacterial cellulose is a hydrogel-like material, the polytetrafluoroethylene rod is used for support), and weaving the degradable fiber on the outer wall of the hollow tubular bacterial cellulose membrane III under the support of the polytetrafluoroethylene rod to form a degradable fiber woven tube on the hollow tubular bacterial cellulose membrane III;
[0025] (3) folding the hollow tubular bacterial cellulose membrane III from one end to the other end along the length direction so that the degradable fiber braided tube is wrapped in the middle to form a three-layer composite tubular object, wherein the outer layer of the three-layer composite tubular object is the tubular bacterial cellulose membrane I, and the inner layer is the tubular bacterial cellulose membrane II, and the outer wall of the tubular bacterial cellulose membrane I has the rectangular groove;
[0026] (4) The obtained three-layer composite tubular object is sterilized to obtain a ureteral stent tube based on bacterial cellulose composite coating.
[0027] According to the method described above, the fermentation strain is one or more of Acetobacter xylinum, Rhizobium, Sarcina, Pseudomonas, Achromobacter, Alcaligenes, Aerobacter and Azotobacter; the fermentation strain is added to the fermentation culture at a density of 10 10 ~10 13 / ml, too low or too high density will affect production efficiency;
[0028] The formula of the fermentation culture medium is as follows: every 100 ml contains 5-30 g of glucose, 1-5 g of peptone, 1-5 g of yeast extract, 0.5-2 g of citric acid, 0.2-5 g of sodium dihydrogen phosphate, 3-5 g of magnesium sulfate, 3-5 g of sodium alginate and the balance of water; the pH value of the fermentation culture medium is 4.0-6.0.
[0029] In the above method, the purification treatment refers to immersing the fermentation product in a sodium hydroxide solution with a concentration of 3 to 10 wt%, maintaining it at a temperature of 30 to 100°C for 3 to 24 hours, and then washing it with water until the pH value is 7.0. A large number of studies have confirmed that the bacterial cellulose membrane purified by sodium hydroxide can have a cellulose purity of more than 99%, and has good biosafety, and can be used in the biomedical field.
[0030] The principle of the present invention is as follows:
[0031] Based on current research and needs, we believe that an ideal ureteral stent should have the following properties: 1. Drain urine and have a certain degree of mechanical support to prevent ureteral stenosis and adhesion blockage; 2. Controllable degradation performance, which can avoid safety issues caused by degradation fragments from a structural design perspective; 3. The surface has a low wet friction coefficient, which facilitates the implantation and removal of the ureteral stent and reduces patient discomfort; 4. Within one month of indwelling a ureteral stent, about 1 / 3 of patients will develop urinary tract infections, so an ideal ureteral stent should have long-lasting antibacterial and broad-spectrum antibacterial properties and low drug resistance; 5. The use of ureteral stents is often due to ureteral damage caused by urinary system diseases in patients. Ureteral stents are used to replace the function of the ureter and temporarily provide drainage and support. If ureteral stents can be used to promote ureteral healing, it will have great practical significance.
[0032] The present invention uses bacterial cellulose and a degradable fiber braided tube capable of sustained-release functional substances to obtain a ureteral stent tube based on bacterial cellulose composite coating. The ureteral stent tube can drain urine and has certain mechanical support to prevent ureteral stenosis and adhesion blockage (mechanical support is mainly provided by the degradable fiber braided tube. Compared with the traditional stent tube, the stent tube obtained by the fiber braiding method of the present invention has better mechanical properties and can also reduce the amount of material used and the wall thickness of the tube wall). The biggest problem restricting the use of degradable ureteral stent tubes at present is the uncontrollable risk caused by the degradation and shedding of materials when the stent tube is used in the body. The present invention uses bacterial cellulose with good biocompatibility in the body to perform surface composite on the degradable braided tube, and folds one end of the hollow tubular bacterial cellulose membrane along the length direction to the other end, thereby forming an inner and outer coating on the degradable fiber braided tube. After implantation in the body, when the degradable braided tube of the middle layer degrades in the body, due to the dense structure formed by the three-dimensional nanofibers of bacterial cellulose, the degraded fragments can be prevented from falling off and directly entering the body, meeting the safety requirements. The surface patterning design of the outer layer of tubular bacterial cellulose reduces surface friction (on the one hand, the surface pattern is along the axial direction, which is more conducive to the entry of the ureteral stent when inserted into the urethra; on the other hand, the surface patterning structure after implantation is more conducive to the growth of surface cells, thereby inhibiting the formation of scar tissue by fibroblasts; it is easier to pull out, thus reducing surface friction) and can promote ureteral healing. In addition, the functional ions released by the degradable fiber have antibacterial and immunomodulatory functions.
[0033] Beneficial effects:
[0034] (1) The bacterial cellulose composite-coated ureteral stent tube of the present invention wraps the braided tube with bacterial cellulose, thereby structurally avoiding the safety problems caused by the shedding of degradation fragments, and has great practical significance;
[0035] (2) The method for preparing a ureteral stent tube based on bacterial cellulose composite coating of the present invention is simple and easy to implement and can be industrially produced. The prepared ureteral stent tube has good comprehensive performance and can meet various requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a schematic structural diagram of a ureteral stent tube based on bacterial cellulose composite coating of the present invention;
[0037] Figure 2 It is a schematic diagram of the hollow tubular bacterial cellulose membrane III folded and coated with a degradable fiber braided tube;
[0038] Figure 3 Schematic diagram of the surface patterning of tubular bacterial cellulose membrane I (having multiple parallel and uniformly arranged rectangular grooves);
[0039] Figure 4 The ion release performance test results of the bacterial cellulose composite-coated ureteral stent prepared in Example 1;
[0040] Among them, 1-outer layer, 2-middle layer, 3-inner layer, 4-hollow tubular bacterial cellulose membrane III. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0042] Example 1
[0043] A method for preparing a ureteral stent tube based on bacterial cellulose composite coating, the specific steps are as follows:
[0044] (1) The fermentation strain (Acetobacter xylinum) and the fermentation culture medium (each 100 ml of the fermentation culture medium contains 5 g of glucose, 1 g of peptone, 1 g of yeast extract, 0.5 g of citric acid, 0.2 g of sodium dihydrogen phosphate, 3 g of magnesium sulfate, 3 g of sodium alginate and the balance of water) are uniformly mixed and placed in a hollow tubular fermentation device. After fermentation for 5 days, the fermentation product is purified (the fermentation product is immersed in a sodium hydroxide solution with a mass concentration of 3 wt%, maintained at a temperature of 100° C. for 3 hours, and then washed with water to a pH value of 7.0) to obtain a hollow tubular bacterial cellulose membrane III; wherein the fermentation strain is added to the fermentation culture medium at a density of 10 10 / ml; The hollow tubular fermentation device is a double-layer jacketed tube, the inner layer of which has an oxygen permeability of 1×10 5 cm 3 / 24h·0.1MPa silica gel film, the fermentation strain and the fermentation culture medium are placed between the double layers of the hollow tubular fermentation device, and the inner layer of the hollow tubular fermentation device is filled with mixed gas, and the pressure of the mixed gas is 1.1×10 5 Pa, the volume proportion of oxygen in the mixed gas is 25%, and the rest is argon; the hollow tubular fermentation device is divided into two hollow tubular objects A and B, the silicone film of the inner layer of the hollow tubular object A has a smooth surface, and the silicone film of the inner layer of the hollow tubular object B has a patterned structure on the outward surface; the patterned structure refers to a plurality of rectangular protrusions formed on the surface of the silicone film by micro / nanoforming patterning technology, which are parallel and evenly arranged along the axis of the hollow tubular object B, the spacing between two adjacent rectangular protrusions is 50nm, the length of the rectangular protrusion is equal to the length of the hollow tubular object B, the width is 50nm, and the height is 50nm;
[0045] (2) placing a polytetrafluoroethylene rod in the purified hollow tubular bacterial cellulose membrane III, and under the support of the polytetrafluoroethylene rod, weaving the degradable fiber on the outer wall of the hollow tubular bacterial cellulose membrane III by a diamond weaving method, and the weaving area is all areas from one end to half the length of the hollow tubular bacterial cellulose membrane III along the length direction, so as to form a degradable fiber woven tube on the hollow tubular bacterial cellulose membrane III; wherein the degradable fiber is a blended fiber of PLA fiber containing silver ions and chitosan fiber containing copper ions and zinc ions, the content of chitosan fiber in the blended fiber is 3wt%, the content of zinc ions is 0.1wt% of the chitosan fiber, and the molar ratio of zinc ions to copper ions is 2:1; the content of silver ions is 0.8wt% of the chitosan fiber;
[0046] (3) Figure 2 As shown, the hollow tubular bacterial cellulose membrane III 4 is folded from one end to the other end along the length direction, so that the degradable fiber braided tube is wrapped in the middle to form a three-layer composite tubular object;
[0047] (4) The three-layer composite tubular product obtained in step (3) is sterilized to obtain a ureteral stent tube based on bacterial cellulose composite coating.
[0048] The final product is a ureteral stent tube based on bacterial cellulose composite coating, such as Figure 1 As shown, it is a three-layer hollow tubular structure with a length of 15 cm, a diameter of 1.5 mm, and a wall thickness of 0.1 mm. The middle layer 2 is a degradable fiber braided tube with a wall thickness of 0.08 mm. The outer layer 1 and the inner layer 3 are tubular bacterial cellulose membranes I and II with the same wall thickness, respectively. The tubular bacterial cellulose membranes I and II are respectively attached to the inner and outer walls of the degradable fiber braided tube; the length of the tubular bacterial cellulose membrane I is half of the hollow tubular bacterial cellulose membrane III; as shown Figure 3 As shown, the outward surface of the tubular bacterial cellulose membrane I has a plurality of parallel and evenly arranged rectangular grooves, the length direction of the rectangular grooves is parallel to the axial direction of the tubular bacterial cellulose membrane I, the spacing between two adjacent rectangular grooves is 50nm, the length of the rectangular groove is 7.5cm, the width is 50nm, and the height is 50nm.
[0049] Related performance tests:
[0050] Biocompatibility test: Referring to the biological evaluation of medical devices in GB / T 16886, the final product, a ureteral stent tube based on bacterial cellulose composite coating, was evaluated for cytotoxicity, guinea pig delayed contact sensitization, skin irritation, etc. The evaluation method is as follows: the intracellular toxicity test is tested in accordance with GB / T 16886-5 "Biological Evaluation of Medical Devices Part 5: In Vitro Cytotoxicity Test"; the guinea pig delayed contact sensitization test is tested in accordance with GB / T 16886-10 "Biological Evaluation of Medical Devices Part 10: Irritation and Delayed Hypersensitivity Test", using the maximum test Magnusson method and Kligman method. The skin irritation test is tested in accordance with GB / T 16886-10 "Biological Evaluation of Medical Devices Part 10: Irritation and Delayed Hypersensitivity Test". Evaluation results: The cytotoxicity of a ureteral stent tube based on bacterial cellulose composite coating prepared in the above Example 1 of the present invention is less than level 1, there is no skin sensitization reaction, no intradermal irritation reaction, and it has good biological safety.
[0051] In vitro degradation experiment: The artificial urine formula is prepared with reference to "YY / T0872-2013 Ureteral Stent Experimental Method", Appendix A, Formula 1. A ureteral stent tube based on bacterial cellulose composite coating prepared in Example 1 of the present invention is sterilized and placed in simulated urine. An in vitro simulated degradation test is carried out in a constant temperature and constant speed shaker at 37°C and 60r / min to observe the degradation of the ureteral stent tube within 5 weeks. The results show that the tubular structure of the test sample is completely degraded within 4 weeks, and the fiber braided structure of the middle layer 2 begins to loosen and break at 3 weeks. Further observation shows that the degraded fibrous material is wrapped between the outer layer 1 and the inner layer 3, and no degradation fragments are freed, indicating that the present invention structurally avoids the safety problems caused by the shedding of degradation fragments.
[0052] Ion release performance test: The content of silver ions, zinc ions and copper ions released from the above simulated urine samples was tested using an atomic absorption spectrometer for 12 days. The test time points were 6h, 12h, 18h, 24h, 48h, 96h, 144h, 192h, 240h and 288h. Ion release rate = ion content in simulated urine at different time points / total ion content in the sample. For test results, see Figure 4 As shown in the figure, the test results show that the ureteral stent of the present invention can continuously and effectively release multiple ions. Among them, silver ions can provide continuous and effective antibacterial properties; zinc ions can run through the entire tissue healing process and meet the release of a large amount in the early stage and also have good continuous release ability in the middle and late stages; in the proliferation and remodeling stage of tissue healing in the middle and late stages, copper ions (Cu 2+ ) can induce the expression of vascular endothelial growth factor, promote angiogenesis, and maintain the stability of collagen.
[0053] Antibacterial performance test: The antibacterial performance of the bacterial cellulose composite-coated ureteral stent prepared in Example 1 was tested using AATCC-100, and the antibacterial rate was 99%. After continuous use for 21 days, the antibacterial performance was tested using AATCC-100, and the antibacterial rate was 99%. The test bacteria were Escherichia coli and Staphylococcus aureus.
[0054] Example 2
[0055] A method for preparing a ureteral stent tube based on bacterial cellulose composite coating, the specific steps are as follows:
[0056] (1) The fermentation strain (rhizobium) and the fermentation culture medium (each 100 ml of the fermentation culture medium contains 5 g of glucose, 1 g of peptone, 1 g of yeast extract, 0.5 g of citric acid, 0.2 g of sodium dihydrogen phosphate, 3 g of magnesium sulfate, 3 g of sodium alginate and the balance of water) are uniformly mixed and placed in a hollow tubular fermentation device. After fermentation for 5 days, the fermentation product is purified (the fermentation product is immersed in a sodium hydroxide solution with a mass concentration of 4 wt%, maintained at a temperature of 80° C. for 3 hours, and then washed with water to a pH value of 7.0) to obtain a hollow tubular bacterial cellulose membrane III; wherein the fermentation strain is added to the fermentation culture medium at a density of 5×10 10 / ml; The hollow tubular fermentation device is a double-layer jacketed tube, the inner layer of which has an oxygen permeability of 1.2×10 5 cm 3 / 24h·0.1MPa silica gel film, the fermentation strain and the fermentation culture medium are placed between the double layers of the hollow tubular fermentation device, and the inner layer of the hollow tubular fermentation device is filled with mixed gas, and the pressure of the mixed gas is 1.1×10 5 Pa, the volume proportion of oxygen in the mixed gas is 25%, and the rest is argon; the hollow tubular fermentation device is divided into two hollow tubular objects A and B, the silicone film of the inner layer of the hollow tubular object A has a smooth surface, and the silicone film of the inner layer of the hollow tubular object B has a patterned structure on the outward surface; the patterned structure refers to a plurality of rectangular protrusions formed on the surface of the silicone film by micro / nanoforming patterning technology, which are parallel and evenly arranged along the axis of the hollow tubular object B, the spacing between two adjacent rectangular protrusions is 50nm, the length of the rectangular protrusion is equal to the length of the hollow tubular object B, the width is 50nm, and the height is 60nm;
[0057] (2) placing a polytetrafluoroethylene rod in the purified hollow tubular bacterial cellulose membrane III, and under the support of the polytetrafluoroethylene rod, weaving the degradable fiber on the outer wall of the hollow tubular bacterial cellulose membrane III by a diamond weaving method, and the weaving area is all areas from one end to half the length of the hollow tubular bacterial cellulose membrane III along the length direction, so as to form a degradable fiber woven tube on the hollow tubular bacterial cellulose membrane III; wherein the degradable fiber is a blended fiber of PLGA fiber containing silver ions and chitosan fiber containing copper ions and zinc ions, the content of chitosan fiber in the blended fiber is 4wt%, the content of zinc ions is 0.3wt% of the chitosan fiber, and the molar ratio of zinc ions to copper ions is 2:1; the content of silver ions is 1.1wt% of the chitosan fiber;
[0058] (3) folding the hollow tubular bacterial cellulose membrane III from one end to the other end along the length direction so that the degradable fiber braided tube is wrapped in the middle to form a three-layer composite tubular object;
[0059] (4) The three-layer composite tubular product obtained in step (3) is sterilized to obtain a ureteral stent tube based on bacterial cellulose composite coating.
[0060] The final product is a ureteral stent tube based on bacterial cellulose composite coating, which is a three-layer hollow tubular structure with a length of 20 cm, a diameter of 1.5 mm, and a wall thickness of 0.1 mm. The middle layer is a degradable fiber woven tube with a wall thickness of 0.10 mm, and the outer layer and the inner layer are tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II with the same wall thickness, respectively. Tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II are respectively bonded to the inner and outer walls of the degradable fiber woven tube; the length of tubular bacterial cellulose membrane I is half of that of the hollow tubular bacterial cellulose membrane III; the outward surface of the tubular bacterial cellulose membrane I has a plurality of parallel and evenly arranged rectangular grooves, the length direction of the rectangular grooves is parallel to the axial direction of the tubular bacterial cellulose membrane I, the spacing between two adjacent rectangular grooves is 50 nm, the length of the rectangular groove is 10 cm, the width is 50 nm, and the height is 60 nm.
[0061] Example 3
[0062] A method for preparing a ureteral stent tube based on bacterial cellulose composite coating, the specific steps are as follows:
[0063] (1) The fermentation strains (Sarcinia and Acetobacter xylinum, the ratio of the two strains is 1:1) and the fermentation medium (each 100 ml of the fermentation medium contains 10 g of glucose, 2 g of peptone, 2 g of yeast extract, 1 g of citric acid, 0.8 g of sodium dihydrogen phosphate, 3.4 g of magnesium sulfate, 3 g of sodium alginate and the rest of water) are uniformly mixed and placed in a hollow tubular fermentation device. After fermentation for 6 days, the hollow tubular bacterial cellulose membrane III is obtained by purification treatment (the fermentation product is immersed in a sodium hydroxide solution with a mass concentration of 5 wt%, maintained at a temperature of 70°C for 6 hours, and then washed with water to a pH value of 7.0); wherein the density of the fermentation strain added to the fermentation medium is 8×10 10 / ml; The hollow tubular fermentation device is a double-layer jacketed tube, the inner layer of which has an oxygen permeability of 2.4×10 5 cm 3 / 24h·0.1MPa silica gel film, the fermentation strain and the fermentation culture medium are placed between the double layers of the hollow tubular fermentation device, and the inner layer of the hollow tubular fermentation device is filled with mixed gas, and the pressure of the mixed gas is 1.2×10 5 Pa, the volume proportion of oxygen in the mixed gas is 28%, and the rest is argon; the hollow tubular fermentation device is divided into two hollow tubular objects A and B, the silicone film of the inner layer of the hollow tubular object A has a smooth surface, and the silicone film of the inner layer of the hollow tubular object B has a patterned structure on the outward surface; the patterned structure refers to a plurality of rectangular protrusions formed on the surface of the silicone film by micro / nanoforming patterning technology, which are parallel and evenly arranged along the axis of the hollow tubular object B, the spacing between two adjacent rectangular protrusions is 80nm, the length of the rectangular protrusion is equal to the length of the hollow tubular object B, the width is 60nm, and the height is 60nm;
[0064] (2) placing a polytetrafluoroethylene rod in the purified hollow tubular bacterial cellulose membrane III, and under the support of the polytetrafluoroethylene rod, weaving the degradable fiber on the outer wall of the hollow tubular bacterial cellulose membrane III by a diamond weaving method, and the weaving area is all areas from one end to half the length of the hollow tubular bacterial cellulose membrane III along the length direction, so as to form a degradable fiber woven tube on the hollow tubular bacterial cellulose membrane III; wherein the degradable fiber is a blended fiber of PGA fiber containing silver ions and chitosan fiber containing copper ions and zinc ions, the content of chitosan fiber in the blended fiber is 6wt%, the content of zinc ions is 0.8wt% of the chitosan fiber, and the molar ratio of zinc ions to copper ions is 2:1.2; the content of silver ions is 1.4wt% of the chitosan fiber;
[0065] (3) folding the hollow tubular bacterial cellulose membrane III from one end to the other end along the length direction so that the degradable fiber braided tube is wrapped in the middle to form a three-layer composite tubular object;
[0066] (4) The three-layer composite tubular product obtained in step (3) is sterilized to obtain a ureteral stent tube based on bacterial cellulose composite coating.
[0067] The final product is a ureteral stent tube based on bacterial cellulose composite coating, which is a three-layer hollow tubular structure with a length of 30 cm, a diameter of 2.0 mm, and a wall thickness of 0.2 mm. The middle layer is a degradable fiber woven tube with a wall thickness of 0.15 mm. The outer layer and the inner layer are tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II with the same wall thickness, respectively. Tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II are respectively bonded to the inner and outer walls of the degradable fiber woven tube; the length of tubular bacterial cellulose membrane I is half of that of the hollow tubular bacterial cellulose membrane III; the outward surface of the tubular bacterial cellulose membrane I has a plurality of parallel and evenly arranged rectangular grooves, the length direction of the rectangular grooves is parallel to the axial direction of the tubular bacterial cellulose membrane I, the spacing between two adjacent rectangular grooves is 80 nm, the length of the rectangular groove is 15 cm, the width is 60 nm, and the height is 60 nm.
[0068] Example 4
[0069] A method for preparing a ureteral stent tube based on bacterial cellulose composite coating, the specific steps are as follows:
[0070] (1) The fermentation strain (Pseudomonas) and the fermentation culture medium (each 100 ml of the fermentation culture medium contains 10 g of glucose, 2 g of peptone, 2 g of yeast extract, 1 g of citric acid, 1.2 g of sodium dihydrogen phosphate, 3.6 g of magnesium sulfate, 4 g of sodium alginate and the balance of water) are uniformly mixed and placed in a hollow tubular fermentation device. After fermentation for 8 days, the fermentation product is purified (the fermentation product is immersed in a sodium hydroxide solution with a mass concentration of 6 wt%, maintained at a temperature of 60° C. for 6 hours, and then washed with water to a pH value of 7.0) to obtain a hollow tubular bacterial cellulose membrane III; wherein the fermentation strain is added to the fermentation culture medium at a density of 2×10 11 / ml; The hollow tubular fermentation device is a double-layer jacketed tube, the inner layer of which has an oxygen permeability of 4×10 5 cm 3 / 24h·0.1MPa silica gel film, the fermentation strain and the fermentation culture medium are placed between the double layers of the hollow tubular fermentation device, and the inner layer of the hollow tubular fermentation device is filled with mixed gas, and the pressure of the mixed gas is 1.2×10 5Pa, the volume proportion of oxygen in the mixed gas is 30%, and the rest is argon; the hollow tubular fermentation device is divided into two hollow tubular objects A and B, the silicone film of the inner layer of the hollow tubular object A has a smooth surface, and the silicone film of the inner layer of the hollow tubular object B has a patterned structure on the outward surface; the patterned structure refers to a plurality of rectangular protrusions formed on the surface of the silicone film by micro / nano molding patterning technology, which are parallel and evenly arranged along the axis of the hollow tubular object B, the spacing between two adjacent rectangular protrusions is 100nm, the length of the rectangular protrusion is equal to the length of the hollow tubular object B, the width is 80nm, and the height is 80nm;
[0071] (2) placing a polytetrafluoroethylene rod in the purified hollow tubular bacterial cellulose membrane III, and under the support of the polytetrafluoroethylene rod, weaving the degradable fiber on the outer wall of the hollow tubular bacterial cellulose membrane III by a diamond weaving method, and the weaving area is all areas from one end to half the length of the hollow tubular bacterial cellulose membrane III along the length direction, so as to form a degradable fiber woven tube on the hollow tubular bacterial cellulose membrane III; wherein the degradable fiber is a blended fiber of PCL fiber containing silver ions and chitosan fiber containing copper ions and zinc ions, the content of chitosan fiber in the blended fiber is 7.5wt%, the content of zinc ions is 1.2wt% of the chitosan fiber, and the molar ratio of zinc ions to copper ions is 2:1.2; the content of silver ions is 2wt% of the chitosan fiber;
[0072] (3) folding the hollow tubular bacterial cellulose membrane III from one end to the other end along the length direction so that the degradable fiber braided tube is wrapped in the middle to form a three-layer composite tubular object;
[0073] (4) The three-layer composite tubular product obtained in step (3) is sterilized to obtain a ureteral stent tube based on bacterial cellulose composite coating.
[0074] The final product is a ureteral stent tube based on bacterial cellulose composite coating, which is a three-layer hollow tubular structure with a length of 30 cm, a diameter of 2.0 mm, and a wall thickness of 0.2 mm. The middle layer is a degradable fiber woven tube with a wall thickness of 0.2 mm, and the outer layer and the inner layer are tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II with the same wall thickness, respectively. Tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II are respectively bonded to the inner and outer walls of the degradable fiber woven tube; the length of tubular bacterial cellulose membrane I is half of that of the hollow tubular bacterial cellulose membrane III; the outward surface of the tubular bacterial cellulose membrane I has a plurality of parallel and evenly arranged rectangular grooves, the length direction of the rectangular grooves is parallel to the axial direction of the tubular bacterial cellulose membrane I, the spacing between two adjacent rectangular grooves is 100 nm, the length of the rectangular groove is 15 cm, the width is 80 nm, and the height is 80 nm.
[0075] Example 5
[0076] A method for preparing a ureteral stent tube based on bacterial cellulose composite coating, the specific steps are as follows:
[0077] (1) The fermentation strain (achromobacter) and the fermentation culture medium (each 100 ml of the fermentation culture medium contains 16 g of glucose, 3 g of peptone, 3 g of yeast extract, 1.2 g of citric acid, 2.4 g of sodium dihydrogen phosphate, 4.1 g of magnesium sulfate, 4 g of sodium alginate and the remainder of water) are uniformly mixed and placed in a hollow tubular fermentation device. After fermentation for 9 days, the fermentation product is purified (the fermentation product is immersed in a sodium hydroxide solution with a mass concentration of 7 wt%, maintained at a temperature of 50° C. for 8 hours, and then washed with water to a pH value of 7.0) to obtain a hollow tubular bacterial cellulose membrane III; wherein the fermentation strain is added to the fermentation culture medium at a density of 6×10 11 / ml; The hollow tubular fermentation device is a double-layer jacketed tube, the inner layer of which has an oxygen permeability of 6×10 5 cm 3 / 24h·0.1MPa silica gel film, the fermentation strain and the fermentation culture medium are placed between the double layers of the hollow tubular fermentation device, and the inner layer of the hollow tubular fermentation device is filled with mixed gas, and the pressure of the mixed gas is 1.2×10 5 Pa, the volume proportion of oxygen in the mixed gas is 32%, and the rest is argon; the hollow tubular fermentation device is divided into two hollow tubular objects A and B, the silicone film of the inner layer of the hollow tubular object A has a smooth surface, and the silicone film of the inner layer of the hollow tubular object B has a patterned structure on the outward surface; the patterned structure refers to a plurality of rectangular protrusions formed on the surface of the silicone film by micro / nano molding patterning technology, which are parallel and evenly arranged along the axis of the hollow tubular object B, the spacing between two adjacent rectangular protrusions is 120nm, the length of the rectangular protrusion is equal to the length of the hollow tubular object B, the width is 100nm, and the height is 80nm;
[0078] (2) placing a polytetrafluoroethylene rod in the purified hollow tubular bacterial cellulose membrane III, and under the support of the polytetrafluoroethylene rod, weaving the degradable fiber on the outer wall of the hollow tubular bacterial cellulose membrane III by a regular weaving method, and the weaving area is all areas from one end to half the length of the hollow tubular bacterial cellulose membrane III along the length direction, so as to form a degradable fiber woven tube on the hollow tubular bacterial cellulose membrane III; wherein the degradable fiber is a blended fiber of PLA fiber containing nanosilver particles and chitosan fiber containing copper ions and zinc ions, the content of chitosan fiber in the blended fiber is 8wt%, the content of zinc ions is 1.5wt% of the chitosan fiber, and the molar ratio of zinc ions to copper ions is 2:1.2; the content of nanosilver particles is 0.1wt% of the chitosan fiber;
[0079] (3) folding the hollow tubular bacterial cellulose membrane III from one end to the other end along the length direction so that the degradable fiber braided tube is wrapped in the middle to form a three-layer composite tubular object;
[0080] (4) The three-layer composite tubular product obtained in step (3) is sterilized to obtain a ureteral stent tube based on bacterial cellulose composite coating.
[0081] The final product is a ureteral stent tube based on bacterial cellulose composite coating, which is a three-layer hollow tubular structure with a length of 35 cm, a diameter of 2.5 mm, and a wall thickness of 0.3 mm. The middle layer is a degradable fiber woven tube with a wall thickness of 0.25 mm. The outer layer and the inner layer are tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II with the same wall thickness, respectively. Tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II are respectively bonded to the inner and outer walls of the degradable fiber woven tube; the length of tubular bacterial cellulose membrane I is half of that of the hollow tubular bacterial cellulose membrane III; the outward surface of the tubular bacterial cellulose membrane I has a plurality of parallel and evenly arranged rectangular grooves, the length direction of the rectangular grooves is parallel to the axial direction of the tubular bacterial cellulose membrane I, the spacing between two adjacent rectangular grooves is 120 nm, the length of the rectangular groove is 17.5 cm, the width is 100 nm, and the height is 80 nm.
[0082] Example 6
[0083] A method for preparing a ureteral stent tube based on bacterial cellulose composite coating, the specific steps are as follows:
[0084] (1) The fermentation strains (Alcaligenes, Rhizobium and Acetobacter xylinum, the ratio of the number of the three strains is 1:1:1) and the fermentation culture medium (each 100 ml of the fermentation culture medium contains 18g of glucose, 4g of peptone, 4g of yeast extract, 1.5g of citric acid, 4.2g of sodium dihydrogen phosphate, 4.5g of magnesium sulfate, 4g of sodium alginate and the balance of water) are uniformly mixed and placed in a hollow tubular fermentation device. After fermentation for 9 days, the fermentation product is purified (the fermentation product is immersed in a sodium hydroxide solution with a mass concentration of 8wt%, maintained at a temperature of 40°C for 10 hours, and then washed with water to a pH value of 7.0) to obtain a hollow tubular bacterial cellulose membrane III; wherein the fermentation strain is added to the fermentation culture medium at a density of 10 12 / ml; The hollow tubular fermentation device is a double-layer jacketed tube, the inner layer of which has an oxygen permeability of 8×10 5 cm 3 / 24h·0.1MPa silica gel film, the fermentation strain and the fermentation culture medium are placed between the double layers of the hollow tubular fermentation device, and the inner layer of the hollow tubular fermentation device is filled with mixed gas, and the pressure of the mixed gas is 1.3×10 5Pa, the volume proportion of oxygen in the mixed gas is 36%, and the rest is argon; the hollow tubular fermentation device is divided into two hollow tubular objects A and B, the silicone film of the inner layer of the hollow tubular object A has a smooth surface, and the silicone film of the inner layer of the hollow tubular object B has a patterned structure on the outward surface; the patterned structure refers to a plurality of rectangular protrusions formed on the surface of the silicone film using micro / nano forming patterning technology, which are parallel and evenly arranged along the axis of the hollow tubular object B, the spacing between two adjacent rectangular protrusions is 150nm, the length of the rectangular protrusion is equal to the length of the hollow tubular object B, the width is 100nm, and the height is 90nm;
[0085] (2) placing a polytetrafluoroethylene rod in the purified hollow tubular bacterial cellulose membrane III, and under the support of the polytetrafluoroethylene rod, weaving the degradable fiber on the outer wall of the hollow tubular bacterial cellulose membrane III by a regular weaving method, and the weaving area is all areas from one end to half the length of the hollow tubular bacterial cellulose membrane III along the length direction, so as to form a degradable fiber woven tube on the hollow tubular bacterial cellulose membrane III; wherein the degradable fiber is a blended fiber of polydioxanone fiber containing nanosilver particles and chitosan fiber containing copper ions and zinc ions, the content of chitosan fiber in the blended fiber is 10wt%, the content of zinc ions is 2.2wt% of the chitosan fiber, and the molar ratio of zinc ions to copper ions is 2:1.3; the content of nanosilver particles is 0.4wt% of the chitosan fiber;
[0086] (3) folding the hollow tubular bacterial cellulose membrane III from one end to the other end along the length direction so that the degradable fiber braided tube is wrapped in the middle to form a three-layer composite tubular object;
[0087] (4) The three-layer composite tubular product obtained in step (3) is sterilized to obtain a ureteral stent tube based on bacterial cellulose composite coating.
[0088] The final product is a ureteral stent tube based on bacterial cellulose composite coating, which is a three-layer hollow tubular structure with a length of 35 cm, a diameter of 2.5 mm, and a wall thickness of 0.3 mm. The middle layer is a degradable fiber woven tube with a wall thickness of 0.3 mm, and the outer layer and the inner layer are tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II with the same wall thickness, respectively. Tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II are respectively bonded to the inner and outer walls of the degradable fiber woven tube; the length of tubular bacterial cellulose membrane I is half of that of the hollow tubular bacterial cellulose membrane III; the outward surface of the tubular bacterial cellulose membrane I has a plurality of parallel and evenly arranged rectangular grooves, the length direction of the rectangular grooves is parallel to the axial direction of the tubular bacterial cellulose membrane I, the spacing between two adjacent rectangular grooves is 150 nm, the length of the rectangular groove is 17.5 cm, the width is 100 nm, and the height is 90 nm.
[0089] Example 7
[0090] A method for preparing a ureteral stent tube based on bacterial cellulose composite coating, the specific steps are as follows:
[0091] (1) The fermentation strain (Aerobacterium) and the fermentation culture medium (each 100 ml of the fermentation culture medium contains 25 g of glucose, 4.5 g of peptone, 4 g of yeast extract, 1.8 g of citric acid, 4.6 g of sodium dihydrogen phosphate, 5 g of magnesium sulfate, 5 g of sodium alginate and the balance of water) are uniformly mixed and placed in a hollow tubular fermentation device. After fermentation for 9 days, the fermentation product is purified (the fermentation product is immersed in a sodium hydroxide solution with a mass concentration of 9 wt%, maintained at a temperature of 35° C. for 12 hours, and then washed with water to a pH value of 7.0) to obtain a hollow tubular bacterial cellulose membrane III; wherein the fermentation strain is added to the fermentation culture medium at a density of 8×10 12 / ml; The hollow tubular fermentation device is a double-layer jacketed tube, the inner layer of which has an oxygen permeability of 9.3×10 5 cm 3 / 24h·0.1MPa silica gel film, the fermentation strain and the fermentation culture medium are placed between the double layers of the hollow tubular fermentation device, and the inner layer of the hollow tubular fermentation device is filled with mixed gas, and the pressure of the mixed gas is 1.5×10 5 Pa, the volume proportion of oxygen in the mixed gas is 40%, and the rest is argon; the hollow tubular fermentation device is divided into two hollow tubular objects A and B, the silicone film of the inner layer of the hollow tubular object A has a smooth surface, and the silicone film of the inner layer of the hollow tubular object B has a patterned structure on the outward surface; the patterned structure refers to a plurality of rectangular protrusions formed on the surface of the silicone film by micro / nanoforming patterning technology, which are parallel and evenly arranged along the axis of the hollow tubular object B, the spacing between two adjacent rectangular protrusions is 150nm, the length of the rectangular protrusion is equal to the length of the hollow tubular object B, the width is 120nm, and the height is 100nm;
[0092] (2) placing a polytetrafluoroethylene rod in the purified hollow tubular bacterial cellulose membrane III, and under the support of the polytetrafluoroethylene rod, weaving the degradable fiber on the outer wall of the hollow tubular bacterial cellulose membrane III by a regular weaving method, and the weaving area is all areas from one end to half the length of the hollow tubular bacterial cellulose membrane III along the length direction, so as to form a degradable fiber woven tube on the hollow tubular bacterial cellulose membrane III; wherein the degradable fiber is a blended fiber of PLGA fiber containing nanosilver particles and chitosan fiber containing copper ions and zinc ions, the content of chitosan fiber in the blended fiber is 12.3wt%, the content of zinc ions is 3.6wt% of the chitosan fiber, and the molar ratio of zinc ions to copper ions is 2:1.4; the content of nanosilver particles is 0.6wt% of the chitosan fiber;
[0093] (3) folding the hollow tubular bacterial cellulose membrane III from one end to the other end along the length direction so that the degradable fiber braided tube is wrapped in the middle to form a three-layer composite tubular object;
[0094] (4) The three-layer composite tubular product obtained in step (3) is sterilized to obtain a ureteral stent tube based on bacterial cellulose composite coating.
[0095] The final product is a ureteral stent tube based on bacterial cellulose composite coating, which is a three-layer hollow tubular structure with a length of 40 cm, a diameter of 3.0 mm, and a wall thickness of 0.4 mm. The middle layer is a degradable fiber woven tube with a wall thickness of 0.4 mm, and the outer layer and the inner layer are tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II with the same wall thickness, respectively. Tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II are respectively bonded to the inner and outer walls of the degradable fiber woven tube; the length of tubular bacterial cellulose membrane I is half of that of the hollow tubular bacterial cellulose membrane III; the outward surface of the tubular bacterial cellulose membrane I has a plurality of parallel and evenly arranged rectangular grooves, the length direction of the rectangular grooves is parallel to the axial direction of the tubular bacterial cellulose membrane I, the spacing between two adjacent rectangular grooves is 150 nm, the length of the rectangular groove is 20 cm, the width is 120 nm, and the height is 100 nm.
[0096] Example 8
[0097] A method for preparing a ureteral stent tube based on bacterial cellulose composite coating, the specific steps are as follows:
[0098] (1) The fermentation strain (nitrogen-fixing bacteria) and the fermentation culture medium (each 100 ml of the fermentation culture medium contains 30 g of glucose, 5 g of peptone, 5 g of yeast extract, 2 g of citric acid, 5 g of sodium dihydrogen phosphate, 5 g of magnesium sulfate, 5 g of sodium alginate and the balance of water) are uniformly mixed and placed in a hollow tubular fermentation device. After fermentation for 9 days, the fermentation product is purified (the fermentation product is immersed in a sodium hydroxide solution with a mass concentration of 10 wt %, maintained at a temperature of 30° C. for 24 hours, and then washed with water until the pH value is 7.0) to obtain a hollow tubular bacterial cellulose membrane III; wherein the fermentation strain is added to the fermentation culture medium at a density of 10 13 / ml; The hollow tubular fermentation device is a double-layer jacketed tube, the inner layer of which has an oxygen permeability of 10×10 5 cm 3 / 24h·0.1MPa silica gel film, the fermentation strain and the fermentation culture medium are placed between the double layers of the hollow tubular fermentation device, and the inner layer of the hollow tubular fermentation device is filled with mixed gas, and the pressure of the mixed gas is 1.5×10 5Pa, the volume proportion of oxygen in the mixed gas is 40%, and the rest is argon; the hollow tubular fermentation device is divided into two hollow tubular objects A and B, the silicone film of the inner layer of the hollow tubular object A has a smooth surface, and the silicone film of the inner layer of the hollow tubular object B has a patterned structure on the outward surface; the patterned structure refers to a plurality of rectangular protrusions formed on the surface of the silicone film by micro / nano molding patterning technology, which are parallel and evenly arranged along the axis of the hollow tubular object B, the spacing between two adjacent rectangular protrusions is 200nm, the length of the rectangular protrusion is equal to the length of the hollow tubular object B, the width is 200nm, and the height is 100nm;
[0099] (2) placing a polytetrafluoroethylene rod in the purified hollow tubular bacterial cellulose membrane III, and under the support of the polytetrafluoroethylene rod, weaving the degradable fiber on the outer wall of the hollow tubular bacterial cellulose membrane III by a regular weaving method, and the weaving area is all areas from one end to half the length of the hollow tubular bacterial cellulose membrane III along the length direction, so as to form a degradable fiber woven tube on the hollow tubular bacterial cellulose membrane III; wherein the degradable fiber is a blended fiber of PCL fiber containing nanosilver particles and chitosan fiber containing copper ions and zinc ions, the content of chitosan fiber in the blended fiber is 15wt%, the content of zinc ions is 5wt% of the chitosan fiber, and the molar ratio of zinc ions to copper ions is 2:1.4; the content of nanosilver particles is 0.1wt% of the chitosan fiber;
[0100] (3) folding the hollow tubular bacterial cellulose membrane III from one end to the other end along the length direction so that the degradable fiber braided tube is wrapped in the middle to form a three-layer composite tubular object;
[0101] (4) The three-layer composite tubular product obtained in step (3) is sterilized to obtain a ureteral stent tube based on bacterial cellulose composite coating.
[0102] The final product is a ureteral stent tube based on bacterial cellulose composite coating, which is a three-layer hollow tubular structure with a length of 40 cm, a diameter of 3.5 mm, and a wall thickness of 0.5 mm. The middle layer is a degradable fiber woven tube with a wall thickness of 0.45 mm. The outer layer and the inner layer are tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II with the same wall thickness, respectively. Tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II are respectively bonded to the inner and outer walls of the degradable fiber woven tube; the length of tubular bacterial cellulose membrane I is half of that of the hollow tubular bacterial cellulose membrane III; the outward surface of the tubular bacterial cellulose membrane I has a plurality of parallel and evenly arranged rectangular grooves, the length direction of the rectangular grooves is parallel to the axial direction of the tubular bacterial cellulose membrane I, the spacing between two adjacent rectangular grooves is 200 nm, the length of the rectangular groove is 20 cm, the width is 200 nm, and the height is 100 nm.
Claims
1. A ureteral stent tube based on bacterial cellulose composite coating, characterized in that: It is a three-layer hollow tubular structure, the middle layer is a degradable fiber braided tube, the outer layer and the inner layer are tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II, respectively, and the tubular bacterial cellulose membrane I and tubular bacterial cellulose membrane II are respectively attached to the inner and outer walls of the degradable fiber braided tube; The tubular bacterial cellulose membrane I and the tubular bacterial cellulose membrane II are formed by folding the hollow tubular bacterial cellulose membrane III from one end to the other end along the length direction, and the length of the tubular bacterial cellulose membrane I is half of that of the hollow tubular bacterial cellulose membrane III.
2. The ureteral stent tube based on bacterial cellulose composite coating according to claim 1, characterized in that: The outward surface of the tubular bacterial cellulose membrane I is provided with a plurality of parallel and evenly arranged rectangular grooves, and the length direction of the rectangular grooves is parallel to the axial direction of the tubular bacterial cellulose membrane I.
3. A ureteral stent tube based on bacterial cellulose composite coating according to claim 1 or 2, characterized in that: The degradable fiber braided tube is obtained by using a diamond braiding or regular braiding method to make degradable fibers capable of slowly releasing functional substances; The degradable fiber capable of sustained-release of functional substances is a blended fiber of synthetic fiber and chitosan fiber, the synthetic fiber is PLA, PLGA, PGA, PCL or polydioxanone fiber, the synthetic fiber contains silver ions or nanosilver particles, and the chitosan fiber contains copper ions and zinc ions.
4. The ureteral stent tube based on bacterial cellulose composite coating according to claim 3, characterized in that: In the degradable fiber capable of sustained-release of functional substances, the content of chitosan fiber is 3 to 15 wt %; The content of zinc ion is 0.1-5wt% of the chitosan fiber, and the molar ratio of zinc ion to copper ion is 2:1-1.4; the content of silver ion or nano silver particle is 0.1-2wt% of the chitosan fiber.
5. The ureteral stent tube based on bacterial cellulose composite coating according to claim 2, characterized in that: The length of the rectangular groove is equal to the length of the tubular bacterial cellulose membrane I, the width is 50 to 200 nm, the height is 50 to 100 nm, and the spacing between two adjacent rectangular grooves is 50 to 200 nm.
6. The ureteral stent tube based on bacterial cellulose composite coating according to claim 1, characterized in that: The length of the ureteral stent tube is 15 to 40 cm, and the diameter is 1.5 to 3.5 mm; the wall thickness of the ureteral stent tube is 0.1 to 0.5 mm, wherein the wall thickness of the degradable fiber braided tube in the middle layer is 0.08 to 0.45 mm, and the wall thickness of the tubular bacterial cellulose membrane I and the tubular bacterial cellulose membrane II are the same.
7. A method for preparing a ureteral stent tube based on bacterial cellulose composite coating as claimed in claim 1, characterized in that: First, a hollow tubular bacterial cellulose membrane III is prepared, and then degradable fibers are woven on the outer wall of the hollow tubular bacterial cellulose membrane III to form a degradable fiber woven tube. Finally, the hollow tubular bacterial cellulose membrane III is folded from one end to the other end along the length direction to form a tubular bacterial cellulose membrane I and a tubular bacterial cellulose membrane II, so that the degradable fiber woven tube is located between the tubular bacterial cellulose membrane I and the tubular bacterial cellulose membrane II, thereby preparing a ureteral stent tube based on bacterial cellulose composite coating. The woven region of the degradable fiber is the outer wall of the tubular bacterial cellulose membrane II.
8. The method according to claim 7, characterized in that The specific preparation steps of the ureteral stent tube based on bacterial cellulose composite coating are as follows: (1) The fermentation strain and the fermentation culture medium are uniformly mixed and placed in a hollow tubular fermentation device. After fermentation for 5 to 9 days, the hollow tubular bacterial cellulose membrane III is obtained by purification treatment; the hollow tubular fermentation device is a double-layer jacketed tube, the inner layer of which has an oxygen permeability of 1 to 10×10 5 cm 3 / 24h·0.1MPa silica gel film, the fermentation strain and the fermentation culture medium are placed between the double layers of the hollow tubular fermentation device, and the inner layer of the hollow tubular fermentation device is filled with mixed gas, and the pressure of the mixed gas is 1.1~1.5×10 5 Pa, the volume proportion of oxygen in the mixed gas is 25-40%; the hollow tubular fermentation device is divided into two hollow tubular objects A and B, the silicone film of the inner layer of the hollow tubular object A has a smooth surface, and the silicone film of the inner layer of the hollow tubular object B has a patterned structure on the outward surface; the patterned structure refers to a plurality of rectangular protrusions formed on the surface of the silicone film by micro / nanoforming patterning technology, which are parallel and evenly arranged along the axis of the hollow tubular object B, the length of the rectangular protrusion is equal to the length of the hollow tubular object B, the width is 50-200nm, the height is 50-100nm, and the spacing between two adjacent rectangular protrusions is 50-200nm; (2) placing a polytetrafluoroethylene rod in the purified hollow tubular bacterial cellulose membrane III, and weaving the degradable fiber on the outer wall of the hollow tubular bacterial cellulose membrane III under the support of the polytetrafluoroethylene rod to form a degradable fiber woven tube on the hollow tubular bacterial cellulose membrane III; (3) folding the hollow tubular bacterial cellulose membrane III from one end to the other end along the length direction so that the degradable fiber braided tube is wrapped in the middle to form a three-layer composite tubular object, wherein the outer layer of the three-layer composite tubular object is the tubular bacterial cellulose membrane I, and the inner layer is the tubular bacterial cellulose membrane II, and the outer wall of the tubular bacterial cellulose membrane I has a rectangular groove; (4) The obtained three-layer composite tubular object is sterilized to obtain a ureteral stent tube based on bacterial cellulose composite coating.
9. The method according to claim 8, characterized in that The fermentation strain is one or more of Acetobacter xylinum, Rhizobium, Sarcina, Pseudomonas, Achromobacter, Alcaligenes, Aerobacter and Azotobacter; the density of the fermentation strain added to the fermentation culture medium is 10 10 ~10 13 Pieces / ml; The formula of the fermentation culture medium is as follows: every 100 ml contains 5-30 g of glucose, 1-5 g of peptone, 1-5 g of yeast extract, 0.5-2 g of citric acid, 0.2-5 g of sodium dihydrogen phosphate, 3-5 g of magnesium sulfate, 3-5 g of sodium alginate and the balance of water; the pH value of the fermentation culture medium is 4.0-6.
0.
10. The method according to claim 8, characterized in that Purification treatment refers to immersing the fermentation product in a sodium hydroxide solution with a mass concentration of 3 to 10 wt%, maintaining it at a temperature of 30 to 100° C. for 3 to 24 hours, and then washing it with water until the pH value is 7.0.
Citation Information
Patent Citations
Gradually degradable woven ureter scaffold tube and preparation method thereof
CN102266594B
Composite material for making degradable ureteral stent and degradable ureteral stent
CN103041454B
Textile multi-component reinforced progressively degradable ureteral stent and its preparation method
CN103211671B
Hollow heterotype bacteria cellulose artificial blood vessel stent material with gradient structure and preparation method thereof
CN103007344A
Natural-blood-vessel-simulating three-layer artificial blood vessel stent and preparation method thereof
CN106540327A